Physical Fitness Among Adolescents Who are Hispanic With Overweight or Obesity. Issue 2 (1st April 2023) - Benzo, Roberto M.; St. George, Sara M.; Messiah, Sarah E.; Lovan, Padideh; Leite, Rafael; Patel, Anmol; Lee, Tae K.; Prado, Guillermo J.
Abstract : Purpose: To describe cardiorespiratory, strength, muscular endurance, and flexibility fitness outcomes in a sample of adolescents who are Hispanic aged 11 to 15 years with overweight or obesity, stratified by age and sex. Methods: The sample included 280 adolescents (mean age: 13.0 ± 0.83 years, mean body mass index percentile: 94.6). Anthropometric measures included height, weight, body mass index percentile, and waist and hip circumference. Fitness measures included handgrip strength, sit-ups in 60 seconds, sit-and-reach test, and 6-minute walk test. We report mean scores for each fitness outcome measure and correlation coefficients with anthropometric measures. Results: Mean handgrip was 23.7 ± 6.48 kg, sit-and-reach test was 25.3 ± 8.13 cm, average sit-ups in 60 seconds were 19.4 ± 9.28, and 6-minute walk distance was 1960 ± 271 ft. Males outperformed females in all tests except sit-and-reach test. Discussion: Compared with published fitness values of healthy weight adolescents, our sample of adolescents who are Hispanic with overweight/obesity living in southern Florida is unconditioned in terms of cardiorespiratory fitness, strength, muscular endurance, and flexibility.